MGL/CLEC10A is an important C-type lectin receptor activated in the innate immune response to Mycobacterium tuberculosis and is suppressed in people with HIV - Browning, Sarah E.; Bharaj, Preeti; Fan, Xiuzhen; Nguyen, Harrison; Holloway, Alex J.; Naqvi, Kubra F.; Lisinicchia, Joshua G.; Paez, Reina N.; Chauhan, Sadhana; Huante, Matthew B.; Martinez-Martinez, Yazmin B.; Endsley, Mark A.; et al. (Frontiers in Immunology, 2025)
Mycobacterium tuberculosis (Mtb) and HIV are leading infectious causes of death worldwide and act synergistically to worsen disease during co-infection. C-type lectin receptors (CLR) respond to pathogen-associated carbohydrates to activate downstream innate immunity and can be exploited for entry of intracellular pathogens. The macrophage (MΦ) galactose-type lectin (MGL, CLEC10A) is an immunomodulatory CLR associated with M2 MΦ. We previously described an immune role for a murine MGL homologue in an experimental model of tuberculosis (TB). Herein we extend these findings by identifying human MGL as an important member of the Mtb-responsive pathogen recognition receptor (PRR) repertoire that is activated in both M1 and M2 polarizing conditions. MΦ exposure to Mtb activates MGL expression and abundant MGL+ cells are present in TB granulomas of human lung and lymph node. Silencing of MGL permits greater Mtb replication in MΦ derived from human peripheral blood monocytes. Compared to healthy controls, MΦ and neutrophils of people with HIV (PWH) have reduced MGL and tissue MGL levels negatively correlate with viral load. Binding assays with recombinant MGL demonstrates direct interaction with Mtb, but not HIV. In vitro Mtb exposure of PBMC from PWH revealed potential recovery of the MGL defect as well as a differential activation of MGL compared to the DC-SIGN and MR CLRs. MGL is thus an important mechanism of innate immunity and potential target for host directed therapy in those with TB or TB-HIV.